The impact of older adult care policy mixes on the construction of senior centers - Chen, Xin (Frontiers in Public Health, 2023)
The problem of an aging population is becoming increasingly serious, and the establishment of senior centers helps to promote the physical health and mental health of the older adult, a key factor in achieving the high-quality development of the old-age security industry. The government has issued a number of policies to promote the establishment and development of senior centers. However, more and more older adult care policy mixes have gradually shown the phenomenon of poor policy connection, confusing standards, and even mutually exclusive content, resulting in many problems in the construction of policy-driven senior centers. Therefore, based on the overall perspective of the older adult care policy mix, this paper uses the GMM method to explore the impact of the comprehensiveness, balance, and consistency of older adult care policy tool portfolios issued by Chinese government agencies on the construction of senior centers in China. The empirical analysis results show that a comprehensive and consistent policy mix can promote the establishment of senior centers, while the balance of the policy mix will inhibit the establishment of senior centers. This paper analyzes the impact of older adult care policy on the construction of senior centers from the perspective of the policy mix, which helps to clarify the different policy effects produced by different policy mix characteristics and provides feasible policy suggestions for the government to formulate more reasonable and effective policies.